Mediterranean diet adherence and sleep pattern: a systematic review of observational studies - Melika fallah; Azadeh Aminianfar; Ahmad Esmaillzadeh (BMC Nutrition, 2024)
Abstract Background and aims Despite a huge body of evidence on the linkage between dietary intakes and pattern of sleeping, the findings are controversial. The current study aimed to summarize earlier findings on the association between adherence to Mediterranean diet (MD) and pattern of sleeping. Methods This study performed based on PRISMA guideline. Systematically search was applied in PubMed, Scopus and Google Scholar to find out relevant publications appeared up to February 2023. No restrictions on language and time of publication were applied. Duplicate citations were removed. We included observational studies which assessed MD as the main exposure and kind of sleep disorders as the main outcome. Results A total of 20 observational studies included. Out of these studies, two were cohort studies and 18 had a cross-sectional design. A total of 21,714 participants included. Usual dietary intakes were assessed using a validated Food Frequency Questionnaire, and a diet history questionnaire. Some studies did not report methods of measuring habitual dietary intakes. Adherence to MD was evaluated by KIDMED questionnaire, PREMED, alternate Mediterranean (aMed) questionnaire, MEDAS questionnaire, MedDietScore, MEDI-LITE score, modified Mediterranean Diet Score (mMDS), Mediterranean food pattern (MFP) and modified Mediterranean diet score (mMED). Pattern of sleeping was examined as sleep quality, sleep duration, sleep latency, sleep efficacy, sleepiness, sleep disturbance, taking a nap and some other sleep disorders. Conclusion In conclusion, findings of published studies highlighted the importance of consumption of MD for better sleep quality.